A novel smart energy network paradigm integrating combined heat and power, photovoltaic and electric vehicles. (15th May 2022) - Calise, Francesco; Cappiello, Francesco Liberato; Dentice d'Accadia, Massimo; Vicidomini, Maria
Abstract: Smart energy networks, based on the integration of thermal and electric technologies, are becoming more attractive to match the increasing energy demand with minimum environmental impact. The design and optimization of a smart energy network based on a combined heat and power system, a photovoltaic solar field, an electric energy storage system and electric vehicles is presented in this work. The investigated system is designed to match the power, heating and cooling demands of a district of 50 residential buildings. The cogeneration system, operating in thermal tracking mode, is based on a reciprocating internal combustion engine, fuelled by natural gas. The engine waste heat is used to match the heating and domestic hot water demands of the residential district. The power produced by both engine and photovoltaic panels is used to match the power demand of the district, including the electric vehicles. The electric energy storage system based on lithium-ion technology is included to shave the peaks of power demand and to decouple demand from supply. The whole system, including all final users, was dynamically simulated in TRNSYS 18. The model was used to develop a case study regarding a district of 50 residential buildings located in Naples (South of Italy). A thermoeconomic optimization of the layout was also performed, using Genopt software. The results of the case study showed that the proposed system exhibits promising performance, reducing CO2 emissions by 62%, with a payback period of 6.39 years. In the optimal scenario, the peak power of the photovoltaic field was found equal to 3.50 MW, with a capacity of the electric energy storage system of 6.70 MWh. The corresponding payback period was equal to 6.31 years.